PENGENDALIAN INTERN PADA SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER - Ahmad Yani (Paradigma, 2008)
An Accounting Information System (AIS) is one of the subjects in a profit-oriented organization. In reality, AIS is very much influenced by the development of information technology, which result numerous computer-based AIS. The implementation of information technology in AIS does not make the system flawless (error free or corruption free). A good accounting information system (manual or computerized) must have a control. An internal control is thus needed to avoid such flaws. Furthermore, an internal control is useful for audit trail. The fact that implementing an internal control to an Accounting Information System is very important makes it a compulsory to create a high standard AIS output. This is like many other systems that are open to any errors or corruptions. The internal control covers the structure of organization, the coordinated methods, and the established measurements of a business organization to keep company’s assets, accuracy and truth of the accounting data as well as the efficiency of company operational.